An existential semantics for habituals - Mendes, Jéssica (Proceedings of the Amsterdam Colloquium, 2025)
This paper focuses on a new observation concerning the interaction of approximatives (almost, barely) and habitual sentences: habituals can only be modified by almost when negated. Based on the distribution of approximatives with nominal quantifiers, I take this pattern as evidence that habituals have an underlying existential force, and acquire their quasi-universal meaning via scalar strengthening.